2002
DOI: 10.1182/blood.v99.4.1314
|View full text |Cite
|
Sign up to set email alerts
|

The chimeric anti-CD20 antibody rituximab induces apoptosis in B-cell chronic lymphocytic leukemia cells through a p38 mitogen activated protein–kinase–dependent mechanism

Abstract: Antibodies against CD20 can activate complement and induce antibody-dependent cellular cytotoxicity (ADCC) in B lymphocytes. In B-cell lines, such antibodies also induce apoptosis. In this study, the expression and function of CD20 on B-cell chronic lymphocytic leukemia (B-CLL) cells were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(136 citation statements)
references
References 30 publications
6
128
2
Order By: Relevance
“…Indeed, in B-CLL, p38 MAPK seems to be involved in the induction of apoptosis either induced by the vitamin D 3 analog EB1089 27 or by the monoclonal antibody rituximab. 28 Pepper et al have reported that the induction of apoptosis by EB1089 is mediated through p38, but chlorambucil-induced apoptosis is not p38 dependent. 27 Pedersen et al 28 have demonstrated dependence on p38 MAPK for the induction of CD20-mediated apoptosis, but complete inhibition of p38 activity resulted only in a partial inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in B-CLL, p38 MAPK seems to be involved in the induction of apoptosis either induced by the vitamin D 3 analog EB1089 27 or by the monoclonal antibody rituximab. 28 Pepper et al have reported that the induction of apoptosis by EB1089 is mediated through p38, but chlorambucil-induced apoptosis is not p38 dependent. 27 Pedersen et al 28 have demonstrated dependence on p38 MAPK for the induction of CD20-mediated apoptosis, but complete inhibition of p38 activity resulted only in a partial inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 Pepper et al have reported that the induction of apoptosis by EB1089 is mediated through p38, but chlorambucil-induced apoptosis is not p38 dependent. 27 Pedersen et al 28 have demonstrated dependence on p38 MAPK for the induction of CD20-mediated apoptosis, but complete inhibition of p38 activity resulted only in a partial inhibition of apoptosis. Both drugs certainly do not induce apoptosis only by activation of p38 MAPK, but apoptosis induced by rituximab or EB1089 may be accompanied by activation of p38.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor studies indicate that this occurs via src-family kinases (Shan et al, 2000). The pleiotropic effects of PLC-g including MAP kinase activation and specifically JNK, ERK and p38MAPK have been implicated in rituximab signaling (Pedersen et al, 2002). PLC-g also cleaves PIP 3 , generating inositol triphosphate and a resultant calcium flux, the latter being implicated in CD20-mediated apoptosis by the observation that intracellular and extracellular calcium chelation each inhibited apoptosis induced by anti-CD20 antibody in RAMOS cells (Hofmeister et al, 2000).…”
Section: Cd20 Binding As a B-cell Signalmentioning
confidence: 99%
“…Crosslinking of Rituximab-induced apoptosis was dependent on the activity of p38MAPK in B-cell chronic lymphocytic leukemia (B-CLL) (Pedersen et al, 2002). Our laboratory has previously reported that Rituximab can reverse in vitro the drug-resistant phenotype of NHL tumor cell lines to a drug-sensitive phenotype (Demiden et al, 1997;Jazirehi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%